AKTIVITAS LARVASIDA EKSTRAK ETANOL DAUN KEMUNING (Murraya paniculata JACK) TERHADAP LARVA Aedes aegypti - Arifani Siswidiasari; Dewa Putu Agus Wahyu Erawan (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2020)
Introduction: A research had been carried out to analyze the larvicidal activity of the ethanol extract of kemuning leaves (Murraya paniculata (L.) Jack.) against Aedes aegypti L. larvae. Method: The research began with extracting yellow leaves (Murraya paniculata (L.) Jack.) With a modified maceration method using 80% ethanol solvent until a thick extract is obtained, then a preliminary test is carried out to obtain LC5 and LC95 so that 5 concentrations of yellow leaf extract (Murraya paniculata (L.) Jack.) can be obtained which can be used as a real larvicide test. The actual larvicide test was carried out with 7 treatments, namely 1 negative control using Tween 80, 5 test treatments namely 1000 bpj yellow leaf extract, 3000 bpj, 5000 ppm, 7000 ppm and 9000 ppm and 1 positive control using Temephos 2 bpj. Observation of the test results was carried out after 24 hours by counting the number of larvae deaths in each treatment group. Result: The data obtained were analyzed by using probit analysis and obtained LC90 of yellow leaf extract (Murraya paniculata (L.) Jack.) which is 8330,291 bpj. The results showed that the yellow leaf extract (Murraya paniculata (L.) Jack.) was effective as a larvicidal activity with LC5 of 1000 bpj and LC95 of 9000 bpj.